Global Research Landscape of Collaborative Learning in Speaking Skills: A Bibliometric Analysis (2016–2025) - Muslim, Muslim; Munirah, Munirah; Bahri, Aliem (PPSDP International Journal of Education, 2025)
This study aims to map and synthesize research trends on collaborative learning in enhancing speaking skills from 2016 to 2025. Using a bibliometric mapping approach, data were retrieved from the Scopus database through a TITLE-ABS-KEY search using the keywords “collaborative learning” and “speaking.” From an initial 610 records, exclusion criteria were applied (2016–2025; document types: article, conference paper, book chapter, review; English only), resulting in 410 documents for analysis. The results show a clear upward trend in publications, with rapid growth in the most recent years. Core dissemination outlets include both language-education journals and technology-oriented proceedings, while author contributions are distributed with a small group of recurring prolific authors. China and the United States are leading contributor countries, and keyword mapping indicates that “collaborative learning” is the central theme, increasingly linked to technology-mediated and AI-related terms in the later period. The novelty of this study lies in providing an integrated Scopus-based bibliometric overview of growth, sources, authors, countries, keywords, and thematic evolution. Practically, findings inform educators and curriculum designers on designing collaborative speaking instruction supported by appropriate learning technologies. This review contributes a structured research landscape and directions for future longitudinal, comparative, and process-focused investigations.